CULTURAL SPECIFICITY OF FRENCH-ITALIAN DRAMA IN EARLY ROCOCO - Данченко, Мария (International Journal of Innovative Technologies in Social Science, 2020)
This article id dedicated to the issue of the genesis of literary rococo in French-Italian drama. In the following article we provide a brief review of theatrical activity of Italian troops in 1660-1720s and explore the formation of new French-Italian Stylistic concepts. Our research focuses particularly on the oeuvre of Luigi Riccoboni, a dramatist of Italian origin and Italian cultural background who wrote numerous scripts for the plays to be performed on French stage. With regard to the lack of studies of these French-Italian plays in Eastern Europe we provide an outline of Luigi Riccoboni's script for comedy "Le Libéral malgré lui" and analyze the intertwinig of Italian and French cultural elements in this play. Our study contributes to clobal research of French rococo in Eastern Europe and explores the aspect of formation of literary rococo in the process of collaboration between Italian and French authors. This article offers a new interpretation of Luigi Riccoboni's oeuvre as that of the first representative of rococo style both in Italian and French literature.